Biosynthesis of nanoparticles using microorganisms: A focus on endophytic fungi - Bartholomew Saanu Adeleke; Olumayowa Mary Olowe; Modupe Stella Ayilara; Oluwaseun Adeyinka Fasusi; Oluwadara Pelumi Omotayo; Ayomide Emmanuel Fadiji; Damian C. Onwudiwe; Olubukola Oluranti Babalola (Heliyon)
The concept of this review underscores a significant shift towards sustainable agricultural practices, particularly from the view point of microbial biotechnology and nanotechnology. The global food insecurity that causes increasing ecological imbalances is exacerbating food insecurity, and this has necessitated eco-friendly agricultural innovations. The chemical fertilizers usage aims at boosting crop yields, but with negative environmental impact, thus pushing for alternatives. Microbial biotechnology and nanotechnology fields are gaining traction for their potential in sustainable agriculture. Endophytic fungi promise to synthesize nanoparticles (NPs) that can enhance crop productivity and contribute to ecosystem stability. Leveraging on endophytic fungi could be key to achieving food security goals. Endophytic fungi explore diverse mechanisms in enhancing plant growth and resilience to environmental stresses. The application of endophytic fungi in agricultural settings is profound with notable successes. Hence, adopting interdisciplinary research approaches by combining mycology, nanotechnology, agronomy, and environmental science can meaningfully serve as potential pathways and hurdles for the commercialization of these biotechnologies. Therefore, setting regulatory frameworks for endophytic nanomaterials use in agriculture, by considering their safety and environmental impact assessments will potentially provide future research directions in addressing the current constraints and unlock the potential of endophytic fungi in agriculture.